Pengaruh Intellectual Capital, Firm Size, Kepemilikan Manajerial dan Corporate Social Responsibility Terhadap Kinerja Keuangan (Studi pada Perusahaan dengan Market Capitalization Terbesar yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2018-2021) - Retno Sudyanti; Nur Diana; Junaidi Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2023)
Intellectual Capital, Firm Size, Managerial Ownership, and Corporate Social Responsibility have a significant influence on the financial performance of a company. This study aims to determine the effect of Intellectual Capital, Firm Size, Managerial Ownership, and Corporate Social Responsibility on Financial Performance in companies with the largest Market Capitalization listed on the Indonesia Stock Exchange (IDX) for the 2018-2021 period. The research sample obtained was 31 companies using the purposive sampling method. Multiple linear regression is a data analysis technique used in this study. The results of the research on Intellectual Capital, Firm Size, and Corporate Social Responsibility have a positive effect on Financial Performance in companies with the largest Market Capitalization listed on the Indonesia Stock Exchange (IDX) for the 2018-2021 period. Managerial Ownership does not affect Financial Performance in companies with the largest Market Capitalization. listed on the Indonesia Stock Exchange (IDX) for the period 2018-2021.Keywords: Intellectual capital, firm size, managerial ownership, corporate social responsibility, market capitalization